2021
DOI: 10.3390/ijms22169083
|View full text |Cite
|
Sign up to set email alerts
|

Diabetic Kinome Inhibitors—A New Opportunity for β-Cells Restoration

Abstract: Diabetes, and several diseases related to diabetes, including cancer, cardiovascular diseases and neurological disorders, represent one of the major ongoing threats to human life, becoming a true pandemic of the 21st century. Current treatment strategies for diabetes mainly involve promoting β-cell differentiation, and one of the most widely studied targets for β-cell regeneration is DYRK1A kinase, a member of the DYRK family. DYRK1A has been characterized as a key regulator of cell growth, differentiation, an… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
10
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
8
1

Relationship

2
7

Authors

Journals

citations
Cited by 13 publications
(10 citation statements)
references
References 199 publications
0
10
0
Order By: Relevance
“…23,[70][71][72] Further diverse roles have been proposed for DYRK1A, including the phosphorylation of tau and amyloid proteins and in regulating pancreatic beta cell proliferation, leading to its investigation as a modulator of diseases ranging from Alzheimer's to diabetes. 71,[73][74][75] Consequently, several DYRK1A inhibitors have been developed which show ontarget efficacy and negligible toxicity in murine models and in a pilot human study, rendering it a key target for further development. [76][77][78] Inhibition of DYRK1A has also recently been reported to alter splicing and increase sensitivity to BCL2 inhibition in non-DYRK1A amplified AML.…”
Section: Discussionmentioning
confidence: 99%
“…23,[70][71][72] Further diverse roles have been proposed for DYRK1A, including the phosphorylation of tau and amyloid proteins and in regulating pancreatic beta cell proliferation, leading to its investigation as a modulator of diseases ranging from Alzheimer's to diabetes. 71,[73][74][75] Consequently, several DYRK1A inhibitors have been developed which show ontarget efficacy and negligible toxicity in murine models and in a pilot human study, rendering it a key target for further development. [76][77][78] Inhibition of DYRK1A has also recently been reported to alter splicing and increase sensitivity to BCL2 inhibition in non-DYRK1A amplified AML.…”
Section: Discussionmentioning
confidence: 99%
“…Numerous pharmacological inhibitors against DYRK1A have been reported [15,17,[41][42][43][44][45][46]. Among these, we selected leucettines, which represent a group of well-characterized DYRK1A inhibitors derived from the leucettamine B (marine sponge alkaloid) (Fig 1) [24,[27][28][29][47][48][49][50][51][52].…”
Section: Pharmacological Inhibitors Of Dyrk1amentioning
confidence: 99%
“…However, numerous biological targets have been studied in this context, including DYRK1A. Studies show that DYRK1A small molecule inhibitors induce human β-cell proliferation both in vitro and in vivo [ 54 , 78 , 114 , 115 , 116 , 117 , 118 ]. Several studies have demonstrated that DYRK1A overexpression attenuated β-cell proliferation through NFAT dysregulation, a transcription factor that transactivates cell cycle-activating genes and represses cell cycle inhibitor genes including other CMGC, cyclins and p57 ( Table 1 ) [ 30 , 68 , 114 , 115 ].…”
Section: Dyrk1a and Other Diseasesmentioning
confidence: 99%